Epidemiological and Aeromedical Risk Assessment of Congenital Heart Disease in Aircrews: A Study at Mohamed V Military Teaching Hospital in Rabat, Morocco - Landing Souané; Zakaria Iloughmane; Meryem Zerrik; Mouna El Ghazi; Fahd Bennani Smires; El Khalifa Sidi Mohamed; Khadidiatou Faye; Fatima Zohra Tlemcani; Maktit Safaa; Isouphou Hamidou Adarka; et al. (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Congenital heart disease (CHD) is the most prevalent congenital disorder. This is one of the most common causes of death derived from malformations. Historically, its treatment has depended on timely diagnosis and early pharmacological and surgical interventions. Survival rates for patients with this disease have increased, primarily due to advancements in therapeutic choices, but mortality remains high. Certain CHD conditions may manifest in individuals already engaged in aircrew duties. It is essential to be able to manage the risk assessment of CHD and to provide appropriate clinical and occupational counsel when deliberating about actual or potential aircrew duties. This study aimed to determine the epidemiological and clinical characteristics of Congenital Heart Disease (CHD) in aircrews. Another aim was to inform decision-making based on clinical risk, aircraft type and aeronautical function. This retrospective cross-sectional study was conducted at the aeromedical Expertise Centre of the Mohamed V Military Teaching Hospital in Rabat, Morocco, from 1 January 2022 to 31 December 2024, covering all aircrew members who were seen during the same period for both admission and review visits. Data were collected and analysed using Jamovi software (version 2.3.28). There were 10737 medical visits, including 6 cases of CHD. The prevalence was 0.55 per 1000 with a sex ratio of 1:1. The average age was 31.7, all civilians. There were 4 admission visits (66.7%), including one class 1 candidate and 3 class four candidates and two revisional visits for a captain and an air hostess. The clinical examination was normal. Electrocardiogram revealed repolarisation disorders in 50% of the individuals, particularly in the septo-apico-lateral and inferior territories. Four had a Myocardial Bridge (MB) and two had an Atrial Septal Defect (ASD) of the Ostium Secundum (OS) type. Four were declared fit (66.66%). The two candidates declared unfit were the air hostess with a wide ASD of 15MM with right heart répercussions and the candidate pilot on admission with MB with a significant MILKING effect of distal LAD. Suitability decisions for candidates with CHD are made on a case-by-case basis. With continued advancements in diagnostics and therapeutics, the number of adults with CHD is expected to rise. Consequently, further longitudinal studies need to be conducted to monitor the interaction of these conditions with the aviation environment and finally to harmonise fitness decisions.